PEMBERDAYAAN MASYARAKAT DALAM PENGOLAHAN LIMBAH ORGANIK - Erviana, Vera Yuli; Mudayana, Ahmad Ahid; Suwartini, Iis (Uhamka Press, 2019)
The local government of Kulonprogo had been making efforts in realizing a zero-waste village. It was proven by the establishment of waste banks with a total of 100 units with no exception in Karangsari village. However, the waste management had not been optimum despite the fact that the waste could be processed into goods with economic value. The limited knowledge and lack of skills became an obstacle in carrying out the waste management. Therefore, there needed to be efforts to improve the human resources in order to conduct both organic and inorganic waste management. The community empowerment towards zero waste village in Karangsari village, Pengasih sub-district, Kulonprogo aimed at creating a healthy environment, providing employment opportunities, creating featured products of environmentally-friendly village and supporting tourism potentials of Kulonprogo in order to increase the community income as well as the regional income. The method used in this study was zero waste industry-based organic and inorganic waste management system. The zero-waste industry concept consisted of actions to reduce, reuse and recycle. The outputs resulted from the study include zero waste industry-based organic and inorganic waste management technique, village featured products of various environmentally-friendly souvenirs, MSME establishment, new employment opportunities and environmental awareness improvement.